HA14-1 is Able to Reconstitute the Impaired Mitochondrial Pathway of Apoptosis in Renal Cell Carcinoma Cell Lines - Sebastian Heikaus; Linda van den Berg; Tobias Kempf; Csaba Mahotka; Helmut Erich Gabbert; Uwe Ramp (Cellular Oncology)
Renal cell carcinomas (RCCs) exhibit a marked resistance towards apoptosis. Although most apoptotic stimuli converge at the level of the mitochondria, little is known about the mitochondrial apoptosis pathway in renal cell carcinomas. The aim of the present study, therefore, was to investigate the functionality of the mitochondrial apoptosis pathway in renal cell carcinoma cell lines by exposure to TRAIL, etoposide, HA14-1 and betulinic acid activating the mitochondria by different mechanisms. Sensitivity to TRAIL-induced apoptosis correlated with cleavage of the initiator caspase-8, but the mitochondrial apoptosis pathway was not induced. Similarly, etoposide and betulinic acid could not induce mitochondrial damage. In contrast, HA14-1 was able to activate mitochondrial apoptosis, thereby demonstrating functionally inducible signalling pathways downstream of the mitochondria. The intactness of the pathways upstream of the mitochondria was shown by pretreatment of TRAIL-sensitive cell lines with HA14-1, which could reconstitute TRAIL-induced mitochondrial damage and resulted in a synergistic apoptosis induction.